Analisis E-Readiness untuk Mempercepat Transformasi Menuju E-Government pada Pemerintah Daerah di Indonesia: Studi Kasus Pemerintah Kabupaten Indragiri Hulu, Provinsi Riau - Zubaidah, Evi; Monalisa; Rusadi, Sylvina; Handoko, Tito (Research and Development Agency Ministry of Home Affairs, 2024)
This research aims to evaluate the readiness of the Indragiri Hulu Regency government, especially Satpol PP and KPBD, to implement the Si ATAN BEDA application, which has been implemented. E-Readiness analysis was carried out using the STOPE approach. The Si ATAN BEDA service application functions as a channel for public complaints, making it easier for the public to submit reports and complaints regarding disturbances of peace, public order, and regional disasters. Implementing the Si ATAN BEDA application service has not shown optimal results due to the government's lack of understanding regarding E-Readiness and making decisions without adequate consideration of the facts. The research method uses a qualitative approach with a descriptive research type. After the field data was collected, the data was processed using NVivo 12 to provide a visual depiction of the field findings and analyzed based on the theory that supports the findings. The results and discussion concluded that the STOPE framework model, which consists of strategy, technology, organization, people, and environment, is the most appropriate model for evaluating the E-Readiness of the Indragiri Hulu Regency government. In the strategy domain, there is a lack of leadership roles in providing direction and supervision, as well as weaknesses in application development planning. The technology domain shows that there are obstacles in application use and security that still need to be strengthened. The lack of cooperation between the government and the private sector in implementing applications is a challenge in the organizational domain. The human resources domain shows that officers' skill qualifications are not aligned with their educational background, and their understanding of applications still needs to be improved. Meanwhile, in the environmental domain of public knowledge, the lack of public knowledge about the application shows a lack of socialization by the government, so the community has not fully felt the benefits.